On Contrasting Expressions of Spatial Deixis in Croatian and English - Žic Fuchs, Milena (1992)
This paper deals with some of the problems connected with contrasting expressions of spatial deixis in Croatian and Englsih. The Croatian sentential demonstratives evo, eto, eno are analysed and contrasted with their English equivalents. Special emphasis is placed on their most frequent, i.e. prototypical uses. Observations are also made on the standard data used in contrastive analysis, and on the importance of including spoken language in contrastive projects. U ovome se radu govori o problemima kontrastiranja prostornih deiktika u hrvatskom i engleskom jeziku. Analizirane su najfrekventnije, tj. prototipične upotrebe rečeničnih demonstrativa evo, eto, eno u hrvatskom i njihovi engleski ekvivalenti. Dotaknut je i problem jezične građe u kontrastivnim projektima, odnosno ograničenja koja proizlaze iz ne- ukljuičivanja govorenog jezika.
Projekt MZOS
ENG